Exploring the natural underground a new sociology of caving - Bingham, Kevin (Abingdon, Oxon ; New York, NY : Routledge, 2023)
This book explores the enigmatic world of the natural underground, viewing it as a site of leisure and a primary sphere of anthropotechnics. It reshapes the old language of caving into new ideas that broaden the possibilities of the sociology of caving. After outlining a novel methodological approach that can be used to understand new leisure trends and cultures in present modernity, Exploring the Natural Underground offers a comprehensive investigation of the societal context in which caving takes place. Thereafter, it goes on to argue that the natural underground can be used as a means of escaping some of the unavoidable influences of consumer capitalism in the way that it stimulates imaginations, senses and emotions differently. Marking a turning point in the way that the natural underground is understood and the degree to which sensory dimensions of leisure are valued, this book will appeal to anybody interested in caving, as well as scholars and students of leisure studies, the sociology of leisure, the ethnography of leisure and human geography.
Keywords: Caving -- Social aspects; Escape (Psychology); Senses and sensation; SPORTS & RECREATION / Sociology of Sports